Book Review: Juan de Dios Ortúzar and Luis G. Willumsen Modelling Transport - van der Hoorn, A.I.J.M (European Journal of Transport and Infrastructure Research, 2002)
his is the third edition of a well-known textbook. Since the success of the first edition, the number of changes has been kept relatively small. It is a very useful book, both for educational purposes and as a reference. There is a good balance between mathematical rigour and practical recommendations. Models are useless without good data and extensive preliminary descriptive analyses and all these three strands are dealt with extensively. Not only "nice" mathematical models, but also "ugly" brute-force models are treated, the latter well-established with (too?) down-to-earth practitioners, The intricate mathematical detail of every model is avoided to concentrate instead on the basic principles and the identification of each model's strengths and limitations. Finally, there are numerous "philosophical" observations and views on the role of transport in contemporary society by two long -term experienced and wise practitioners. Does anything remain to be desired? Of course. The original version of the book contained quite a number of errors and mistakes, probably to the desperation of beginning scholars. Furthermore, at the end of each chapter a small number of useful exercises is included, but these are definitely not paper - and - pencil exercises, and it is not always clear beforehand which instruments are needed to solve them. Finally, what I would like to see is a more complete description of public transport assignment, because this is not only useful for public transport, but also for wider application as in airline transport and airport choice.